Physicochemical qualities and antioxidant properties of juice extracted from ripe and overripe wax apple as affected by pasteurization and sonication - Sri Charan Bindu Bavisetty; Karthikeyan Venkatachalam (My University, 2021)
The present study investigated the effect of sonication alone and sonication with subsequent pasteurization on physicochemical and antioxidant properties of juice extracted from the ripe or overripe wax apple. Samples were sonicated for varying times (0–10 min) at a fixed frequency (28 kHz) and temperature (20°C) and then, pasteurized at 90°C for 2 min. Irrespective of the maturity, sonication improved the color characteristics (lightness, chroma, and hue) of wax apple juices (p > .05). Other quality parameters (titratable acidity, total soluble solids, cloud value and electrical conductivity) exhibited similar changes for all the juice samples tested. Sonicated samples retained higher antioxidant activity (5%–30%), especially in the ripe juice, whereas pasteurization significantly reduced (5%–20%) the antioxidant activity, as well as the total phenolic content. Moreover, sonication significantly reduced the enzyme activities, including polyphenol oxidase, polygalacturonase, pectin methylesterase, and peroxidase by 2%–10% when compared with pasteurization. Overall, sonication, either individually or in conjunction with pasteurization or thermal processing, was beneficial for maintaining the quality by inactivating enzymes, and retaining nutrients, whereas pasteurization degraded these juices. Novelty impact statement Ripe and overripe wax apple fruit juice was treated by pasteurization and sonication. Sonicated ripe wax apple juice was found to improve various phytochemical contents and antioxidant activities. Pasteurized and as well as sonicated ripe and overripe wax apple juice were effectively controlled the activities of quality degrading enzymes such as polyphenol oxidase, polygalacturonase, pectin methylesterase, and peroxidase
Keywords: Pasteurization; Sonication; Browning; Pectin; Titratable acid; Postharvest Quality and Shelf Life Management